Use of upadacitinib in the treatment of moderate to severe atopic dermatitis: patient profiling, dose selection, and therapy modulation, what does real-life teach us? - Edoardo Mortato; Niccolò Gori; Giacomo Caldarola; Marina Talamonti; Claudia Paganini; Luisa Boeti; Filomena Russo; Teresa Grieco; Ersilia Tolino; Gaia Moretta; Flavia Pigliacelli; Rosa Coppola; et al. (Journal of Dermatological Treatment)
Purpose This multicenter retrospective study assessed the real-world effectiveness and safety of upadacitinib in adults with moderate-to-severe atopic dermatitis across eight centers in central Italy.Materials and methods A total of 150 patients received upadacitinib 15 mg or 30 mg daily as monotherapy. Clinical outcomes were evaluated up to 104 weeks using Eczema Area and Severity Index (EASI), itch and sleep numeric rating scale (NRS), and Dermatology Life Quality Index (DLQI).Results Both dosages led to significant and sustained improvements in disease severity, pruritus, sleep disturbances, and quality of life, with 77.8% achieving EASI 75 and 39.2% achieving EASI 100 at week 16. Responses were similar between doses, although long-term itch control was better in the 30 mg group. Higher baseline EASI score was a positive predictor of response, while head and neck involvement and prior systemic treatments, particularly cyclosporine, were associated with poorer outcomes. The safety profile was consistent with prior reports, with acneiform eruption, elevated creatine phosphokinase (CPK), and dyslipidemia being the most common adverse events. No reactivation of atopic keratoconjunctivitis was observed.Conclusions These findings support the efficacy, safety, and flexibility of upadacitinib dosing in clinical practice.